Kajian Garap Kendang Pada Gending Kagok Respati - Harun Isma'il (DESKOVI : Art and Design Journal, 2022)
This research is entitled "Study of Garap Kendang on Gending Kagok Respati". The research aimsto explain and analyze in depth one musical case of garap kendangan. The garap kendangan is focused on the gending of Kagok Respati. The problems revealed are related to the way of serving gending and the application of kendang instrument play to the Kagok Respati gending. Both problems were studied using the concept of garap. To obtain results that were as expected, this study used qualitative research methods with a discriptive analysis approach. A discriptive approach to analysis is used to explain the shape and structure of the kagok respati gending kendangan pattern. Based on the results of the analysis, it was concluded that the road of serving gending Kagok Respati starts from buka, merong, umpak inggah, inggah, and suwuk. The pattern of the kendangan gending Kagok Repati part of the merong uses a kendangan setunggal merong kethuk 2 (loro) laras pelog. In the inggah section, it uses a Surakarta-style ciblon kendangan.